Diphenylsilane‐Manganese Acetylacetonate Redox Initiating Systems: Toward Amine‐Free and Peroxide‐Free Systems. Issue 11 (10th May 2020) - Arar, Ahmad; Mousawi, Assi Al; Boyadjian, Cassia; Garra, Patxi; Fouassier, Jean Pierre; Lalevée, Jacques
Abstract: Room temperature redox initiated free radical polymerization (RFRP), without light, brings a significant breakthrough in the field of materials science including energy conservation, high efficiency, robustness in thick materials/composites, and easy operation. Meanwhile, the current redox initiating systems used are based on toxic aromatic amines and hazardous peroxides (e.g., dibenzoylperoxide). In the present paper, for the first time in literature, new amine‐free, peroxide‐free redox two component (2K) initiating systems comprised of diphenylsilane (DPS, a reducing agent) and manganese acetylacetonate (Mn(acac)3, an oxidizing agent) are proposed. The significance of the system is its applicability under mild conditions (RT, under air). Optical pyrometry measurement results showed that the DPS in combination with Mn(acac)3 exhibited an excellent radical initiating property for benchmark (meth)acrylate monomers, competitive with a well‐established amine/dibenzoyl peroxide reference. Based on electron spin resonance experiments, the initiating chemical mechanisms of RFRP are proposed. Abstract : A new redox free radical initiating system is discovered for (meth)acrylate polymerization, it is based on a Mn(acac)3/diphenylsilane interaction. Three advantages are found: i) avoid pressing regulations on peroxides by choosing Mn oxidizing agent; ii) avoid toxic/carcinogenic amine; and iii) easy tuning of gel time by selection of appropriate concentrations and/or additives .